Why the third way failed economics, morality and the origins of the "Big Society" - Jordan, Bill 1941- (Policy Press, 2010)
This insightful and progressive book proposes a new moral approach to public policy to replace Third Way governments' failed attempts to reconcile global markets with ethically-informed public policies
Title from publisher's bibliographic system (viewed on 01 Sep 2022)
Keywords: Public welfare / Great Britain; Social policy / Moral and ethical aspects; Great Britain / Economic policy / 1997-; Great Britain / Politics and government / 1997-2007; Great Britain / Social policy